2022
DOI: 10.1186/s40538-022-00284-5
|View full text |Cite
|
Sign up to set email alerts
|

Plastic film mulching with ridge planting alters soil chemical and biological properties to increase potato yields in semiarid Northwest China

Abstract: Background The growth of potato (Solanum tuberosum L.) is severely affected by the complex and variable soil environment, and film mulching has been widely used for potato growth in semiarid areas of western China. However, there are few studies on the effects of film mulching on soil quality and tuber yield in potato fields. Methods The effects of four mulching patterns (flat plot without film mulching, FP; flat plot with film mulching, FPM; ridge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
2
4
1
Order By: Relevance
“…Previous research found that mulching practices had less significant influence on the SOC content when growing wheat and maize (Yu et al, 2021), similar to our results during the mature period of proso millet in all three regions. This may be because mulching practices increase the mineralization and turnover of SOC, resulting in no significant change in the SOC contents (Shi et al, 2022).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Previous research found that mulching practices had less significant influence on the SOC content when growing wheat and maize (Yu et al, 2021), similar to our results during the mature period of proso millet in all three regions. This may be because mulching practices increase the mineralization and turnover of SOC, resulting in no significant change in the SOC contents (Shi et al, 2022).…”
Section: Discussionsupporting
confidence: 73%
“…Previous studies support our findings (Chen et al, 2021; Cui et al, 2020; Liu et al, 2022). These results suggested increases in soil extracellular enzyme activity can improve soil nutrients (Shi et al, 2022). In all three regions, PFM and RF distinctly impacted the soil extracellular enzyme activity, confirming previous reports that the types of mulching technique also influenced the levels of extracellular enzymes (Shi et al, 2022; Zhang, You, et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…was affected by lm mulching. Mulching was able to increase biomass and raise soil temperature, promote plant growth, and increase plant biomass and yield when compared to the NFM treatment (Mo et al, 2020;Niu et al, 2020;Shi et al, 2022). However, the aboveground biomass of C. esculentus rst increased and then decreased with increasing irrigation, and the above-underground biomass reached the maximum value in the T2 treatment.…”
Section: Response Of Nutrient Content and Stoichiometric Characterist...mentioning
confidence: 88%
“…Similar observations have been confirmed in several kinds of literature (Akhtar et al, 2018; Wang, Wang, et al, 2021). Overall, the improvement of rhizosphere soil enzyme activities indicated that the soil quality might be improved, which may be attributed to variations in the number of soil microorganisms in the mulching regimes, and there are differences in the catabolic capacity of soil microorganisms, thereby impacting the enzyme activities (Mendonça et al, 2021; Shi et al, 2022).…”
Section: Discussionmentioning
confidence: 99%